Immunization Status Of Lame Children In Aligarh District - Kumar, Neelam; Khan, A Z (Indian Journal of Community Health, 1997)
Research Problem:Immunization profile of under five lame children in district Aligarh. Objectives: i) To assess the prevalence of lameness among polio vaccinated and unvaccinated children. ii) To assess lameness in relation to their overall immunization status and source of immunization. Study Design : Cross - sectional epidemiological study. Participants: Under five children. Sample Size: 10,020 under five children drawn from 30 clusters of Aligarh district. Study Variable: Immunization status of participant children. Outcome Variable: Lameness among immunized and unimmunized children. Statistical Analysis: Tests of proportion. Result: Among the vaccinated (had at least one dose of OPV) children , prevalence of lameness was 2.0/1,000, while among unvaccinated children, prevalence was 8.8/1,000. This difference was statistically significant (X3= 30, d.f. = 1 P < 0.001). Conclusion and Recommendations: i)Immunization of target children with OPV is an effective preventive measure to lower down the prevalence of lameness in children, ii) Apart from continuing routine immunization, there is need of gearing up catch - up and mop - up rounds of polio immunization. iii) The strategy of pulse polio immunization is needed to be executed year after year until poliomyelitis is eradicated. iv) Community based surveillance and sentinel surveillance of poliomyelitis should be expanded to all remote and far flung areas.